Downregulation of Elovl5 promotes breast cancer metastasis through a lipid-droplet accumulation-mediated induction of TGF-β receptors - Trinh-Le-Vi Kieu; Léa Pierre; Valentin Derangère; Sabrina Perrey; Caroline Truntzer; Antoine Jalil; Sébastien Causse; Emma Groetz; Adélie Dumont; Laura Guyard; Laurent Arnould; Jean-Paul Pais de Barros; et al. (Cell Death and Disease, 2022)
Abstract Metastatic breast cancer cannot be cured, and alteration of fatty acid metabolism contributes to tumor progression and metastasis. Here, we were interested in the elongation of very long-chain fatty acids protein 5 (Elovl5) in breast cancer. We observed that breast cancer tumors had a lower expression of Elovl5 than normal breast tissues. Furthermore, low expression of Elovl5 is associated with a worse prognosis in ER+ breast cancer patients. In accordance with this finding, decrease of Elovl5 expression was more pronounced in ER+ breast tumors from patients with metastases in lymph nodes. Although downregulation of Elovl5 expression limited breast cancer cell proliferation and cancer progression, suppression of Elovl5 promoted EMT, cell invasion and lung metastases in murine breast cancer models. The loss of Elovl5 expression induced upregulation of TGF-β receptors mediated by a lipid-droplet accumulation-dependent Smad2 acetylation. As expected, inhibition of TGF-β receptors restored proliferation and dampened invasion in low Elovl5 expressing cancer cells. Interestingly, the abolition of lipid-droplet formation by inhibition of diacylglycerol acyltransferase activity reversed induction of TGF-β receptors, cell invasion, and lung metastasis triggered by Elovl5 knockdown. Altogether, we showed that Elovl5 is involved in metastasis through lipid droplets-regulated TGF-β receptor expression and is a predictive biomarker of metastatic ER+ breast cancer.